2020
DOI: 10.1007/s12551-020-00673-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific characteristics of macromolecules create specific effects in living cells

Abstract: Recently, the important role of microphase separation in living cells has been attracting considerable interest in relation to cell organization and function. For example, many studies have focused on liquid-liquid phase separation (LLPS) as a very plausible mechanism for the presence of membraneless organelles. To confirm the role of phase separation in living cells, experimental studies on models and/or reconstructed systems are needed. In this short review, we discuss current paradigms of LLPS and provide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Figure 2 b shows that the epithelial cells are localized on the interface of the w/w droplets, where fluorescence is emitted by mCherry expressed inside the cells. A similar localization of RBC and epithelial cells for w/w droplets in a PEG/DEX solution was observed under non-confinement conditions in the 3D experimental system as recently reported 33 , 34 . Figure 2 c shows the generation of the droplet array entrapping DNA molecules, where DNAs are stained by YOYO-1.…”
Section: Resultssupporting
confidence: 86%
“…Figure 2 b shows that the epithelial cells are localized on the interface of the w/w droplets, where fluorescence is emitted by mCherry expressed inside the cells. A similar localization of RBC and epithelial cells for w/w droplets in a PEG/DEX solution was observed under non-confinement conditions in the 3D experimental system as recently reported 33 , 34 . Figure 2 c shows the generation of the droplet array entrapping DNA molecules, where DNAs are stained by YOYO-1.…”
Section: Resultssupporting
confidence: 86%
“…Yoshikawa and his colleagues have demonstrated that double-stranded DNA (dsDNA) undergo soluble/insoluble transition as a first-order phase transition. This sharp transition can be induced by various chemical stimuli, including polycations, neutral polymers, divalent/trivalent cations, and even polyanions 52 . Eukaryotic chromosomes are known to be organized in numerous micrometer-sized DNA "puffs" that are approximately 1 megabase in length 53 ; it is physically possible that small changes in the local chemical environment induce the phase separation of each individual puff independently.…”
Section: Stickiness As the Source Of Evolvabilitymentioning
confidence: 99%
“…But considering the highly condensed cellular environment, the demonstrations by the Yoshikawa group, and the growing evidence for the existence and biological function of membrane-less organelle64 , it is likely that solution properties of biomolecules should have the evolvability of TF-biosensors. By considering the designed biomolecules' physicochemical dynamics, including aggregative65 , kinetic, and phase separational52,55,64 , directed evolutionists can maximize the evolvability of the TF-biosensors.15H04189, 15K14228, 16H 06450]. D.U.…”
mentioning
confidence: 99%
“…The bulk of the Special Issue was composed of numerous review articles (forty-five) chosen from the nearly thirty separate sections of the BSJ’s national society meeting. A short selection of these (many) interesting review articles includes those dealing with the biophysics of chromatin (Ashwin et al 2020 ; Kumar and Kono 2020 ); optogenetics (Kandori 2020 ); computational structure prediction (Kinoshita and Hayashi 2020 ; Leitner and Yamamoto 2020 ; Tsuchiya and Tomii 2020 ); physical biochemistry (Tsumoto et al 2020 ); molecular motors (Li and Toyabe 2020 ; Loutschko and Flechsig 2020 ; Noji et al 2020 ); membrane protein interaction (Moghal et al 2020 ); novel scattering, structural and imaging techniques (Nakasako et al 2020 ; Uchihashi and Ganser 2020 ; Yamaoki et al 2020 ; Yokoyama et al 2020 ); cellular biophysics (Okazaki et al 2020 ; Yasuda 2020 ); biophysical thermochemistry (Fukuyama and Maeda 2020 ; Suzuki and Plakhotnik 2020 ); and biophysical theory (Leitner and Yamamoto 2020 ; Uda 2020 ).…”
Section: Highlights Of 2020mentioning
confidence: 99%